The Correlation Between Students' Response To English Teachers' Methods And Their Motivation In Learning English - Rohani, Rohani; Ari Prasetyaningrum; Siti Masyuroh; Usuluddin, Usuluddin (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study examines the correlation between students’ responses to English teachers’ instructional methods and their motivation to learn English. Recognizing the significance of motivation in language teaching, the study aims to explore how different teaching methods impact both student engagement and intrinsic motivation. Using a quantitative correlational research design, data were collected from 33 eighth-grade students at MTs Muallimat NWDI Pancor in the 2024-2025 academic year. The analysis reveals a strong positive correlation between students’ responses to teaching methods and their learning motivation (r = 0.642, p < 0.01) as well as between teaching methods and student motivation (r = 0.701, p < 0.01). These findings suggest that teaching methods significantly influence both student engagement and motivation; efficient, student-centered methods lead to greater student involvement in the learning process and higher motivation levels. The study recommends that schools prioritize continuous professional development for teachers, focusing on effective, motivational teaching strategies. This would foster an engaging, supportive learning environment, enhancing students’ ability to succeed in language learning. The findings contribute to a deeper understanding of the interaction between pedagogy and student psychology, providing valuable insight for both educational practitioners and policymakers.